PENGARUH INTENSITAS PEMAKAIAN GADGET TERHADAP PERKEMBANGAN EMOSI PADA ANAK USIA PRA SEKOLAH: LITERATURE REVIEW - Nur Fitri Farkhana; Yuan Fyrraliany; Dini Nur Alpiah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
In the current era of globalization, gadgets play a large role in conveying information and social interaction. Children who often use gadgets often forget their surroundings. Children are more interested in playing using gadgets than playing together with friends in the surrounding environment. So what happens is that social interaction between children and the surrounding environment decreases. This research aims to determine the effect of intensity of gadget use on emotional development in pre-school children. The research used the Literature Review method, carried out using the PICO search in the Google Scholar database. There were 5 journals that met the criteria and showed the results of the influence of the intensity of gadget use on emotional development in pre-school children.